Phase II trial protocol of focal prostate ablation combined with androgen deprivation therapy for prostate cancer treatment - Jason Koehler; Daniel Lama; Megan Mendez; Wei-Wen Hsu; Aytekin Oto; Russell Szmulewitz; Abhinav Sidana (PLoS ONE, 2025)
Background Prostate cancer (PCa) is one of the most commonly diagnosed cancers. Treatments for PCa with less adverse effects than whole gland interventions, such as focal therapy (FT), often involve a higher risk of PCa recurrence. Combining FT with other treatments could increase the efficacy while maintaining a low side effect profile. This study aims to determine the proportion of residual/recurrent clinically significant PCa following the combination treatment of three months of androgen deprivation therapy (ADT) and FT of the prostate, as well as the safety of this treatment regimen. Methods This study will be a single arm phase II trial with a recruitment goal of 57 patients with treatment naïve non-metastatic intermediate risk PCa. Patients will complete the I-PSS, SHIM, and EPIC-26 questionnaires at the screening visit. Patients will then comply with a three-month treatment course of ADT. Eight weeks after beginning ADT, patients will undergo FT of the prostate via high intensity focused ultrasound or cryoablation. Follow up visits will occur every three months for a year post FT to monitor for side effects, repeat questionnaires, perform a clinical assessment, and obtain PSA and testosterone values. Twelve months after FT, a surveillance multiparametric MRI and MRI-targeted biopsy will be performed to assess for treatment failure. Discussion The primary endpoint of this trial is to determine the proportion of men with clinically significant PCa as evaluated by a surveillance mpMRI and MRI-TB at 12-months following FT. If successful, this treatment approach could offer a new option for treatment with fewer side effects than whole gland interventions and more efficacy than FT alone. Furthermore it could inform the need for further research into multimodal treatment options for PCa. Clinical trial registration ClinicalTrials.gov, NCT05790213. Registered on March 30, 2023.